PROJECT-BASED LEARNING THROUGH MULTIPLE ORAL PERFORMANCE MODES: A QUALITATIVE EXPLORATION OF EFL SPEAKING DEVELOPMENT IN HIGHER EDUCATION - Yulianti Yulianti; Ahmad Bukhori Muslim; Wawan Gunawan (English Study Program University of Pasir Pengaraian, 2026)
Developing speaking skills remains a significant challenge for English as a Foreign Language (EFL) learners in higher education. While Project-Based Learning (PBL) has been recognized as an effective student-centered approach, limited studies have explored the integration of presentation, storytelling, and debate activities within a single project framework to enhance speaking proficiency. This study aims to investigate the implementation of PBL and examine its contribution to students’ speaking development. A qualitative case study design was employed involving EFL students enrolled in speaking courses at a higher education institution. Data were collected through classroom observations, semi-structured interviews, recall interviews, speaking performance assessments, and document analysis. The findings reveal that PBL was implemented through five stages: project planning, collaborative inquiry, project development, oral performance implementation, and reflection. The integration of presentation, storytelling, and debate activities improved students’ fluency, pronunciation, vocabulary mastery, grammatical accuracy, and communicative competence. Furthermore, students reported increased confidence, motivation, classroom participation, and willingness to communicate, while experiencing lower levels of speaking anxiety. These findings suggest that PBL provides authentic learning experiences that effectively support speaking development and foster positive learner engagement in EFL contexts.